The involvement of employees in knowledge management in the light of the research results - Janina Stankiewicz; Marta Moczulska (Institute of Economic Research (IER), 2014)
The development of information technology, increase demand for mental work, shortening product life cycle and competing of the quality meant that knowledge is widely considered to be one of the most important resources of the organization. Taking into account activities related to the process of knowledge management (such as the acquisition of knowledge from the environment, identifying its in the organization, knowledge sharing) and their sources (internal and external stakeholders) can be noted that any knowledge management requires the involvement of employees. Based on the analysis of the employees engagement was found that managing knowledge should be supported by the affective commitment and focused on work organization and environment. They exhibit a specific behavior. Recognizing this problem for interesting the empirical research was carried out. Their goal was to identify the prevalence of involvement of employees in knowledge management and the desired employee behavior in the various activities of this processes. The study conducted among enterprises of Lubuskie province. The research used a survey method. It was found that the surveyed enterprises implement the activities related to knowledge management in a selective manner. In the light of the adopted criteria only one (out of 102) of the surveyed companies could be considered as knowledge management. It also seems that the attention is not focused on the creation of knowledge but its acquisition and protection. Taking into account the results of research on behavior conducive to knowledge management can be concluded that the climate for creativity exists at the level of teams but not the organization.
Keywords: D83; 330; employees involvement; knowledge management; process; activity; behaviour